Počasne spremembe podjetniške stvarnosti: GEM Slovenija 2006 - Rebernik, Miroslav; Tominc, Polona; Pušnik, Ksenja (University of Maribor Press, 2007)
Slow Changes of Entrepreneurial Reality : GEM Slovenia 2006. Entrepreneurship, with its many faces, is defined by researchers in various ways, and the general public usually understands and interprets it also quite differently. Entrepreneurship is a process in which individuals decide to pursue an entrepreneurial career. Based on the Global Entrepreneurship Monitor (GEM) data we can identify individuals between the ages of 18 and 64 who have either taken some action towards creating a new business or have already established one. As GEM methodology is same for all years, GEM data provides a good understanding of entrepreneurial changes. Data shows that in Slovenia the motivation index has been on the increase during the past five years: an increasing number of individuals has started entrepreneurial activity out of opportunity. This is important because necessity-driven entrepreneurs have lower growth ambitions and exhibit lower employment and development tendencies than opportunity-driven entrepreneurs. As addition, present study emphasizes one of essential components of the entrepreneurial process which is venture financing.